Measuring the Results of Manchester United Social Media Strategy - Rasyid, Hafiyyan; Iskandar, Budi Permadi (Journal of Business and Management, 2017)
Abstract Engagement is one of important things for a brand. Engagement is formed because there is a relationship between brand and its customers through a two-way communication process. This communication can be carried out by using social media especially Instagram. The brand gives information which is designed to attract its customers. If the customers are interested, they will give feedback through likes, comments or shares. Social media manager has to be able to deliver attractive contents and has a strategy to share the contents. The aim of this study is to formulate the role of social media manager especially in football. The first step is to determine clubs which will be chosen as a research object based on the number of followers. The next step is to categorize kinds of contents which are shared by each club. The last step is to measure engagement and to analyze a strategy from each club in sharing each its content. The result of this study is Manchester United shares all kinds of contents, has higher engagement than other clubs, results player’s contract content as the most interested content and has a strategy in sharing contents that is not like other clubs. Keywords: social media, instagram, engagemet, manchester united